The effect of bank ownership and deposit insurance on monetary policy transmission - Andries, Natalia; Billon, Steve (Journal of Banking & Finance, 2010)
In this paper we develop a theoretical model with a representative bank whose ownership is shared between state and private sector. The bank faces a risk of failure and provides private and public explicit deposit insurance. Banks owned to a larger extent by the government are more able to counteract a restrictive monetary policy because of their capacity to raise additional volume of deposits. Therefore, the greater the state’s share in the bank ownership, the less the impact of a monetary tightening on the level of loan supply.